Study of replacement of sand using foam concrete - Yeong, Choong Li (Universiti Malaysia Sarawak (UNIMAS), 2009)
Foam concrete has been a subject of interest in Civil Engineering field for many years. Yet, so far there are not much research had been done on the possibility of using foam concrete as a backfill material. Due to the properties of foam concrete which is light in weight and thus low in density, this research has been designed in a way that the feasibility of using foam concrete as a floating foundation is carried out. In this study of replacing sand using foam concrete, there were two sets of tests which were carried out. The methodology of this study was designed together with experienced long time researcher in concrete technology, Dr Mohd Ibrahim Safawi Hj. Mohd. Zain, together with Master Degree student Mr Lai Phui Hua. The samples of foam concrete were produced in the laboratory of UNIMAS Concrete Laboratory. The research is mainly focused on the possibility to use foam concrete as a...